An inverted U-shaped association between high-sensitivity C-reactive protein and the albumin ratio and hepatic steatosis and liver fibrosis: a population-based study - Ma, Xiaorong; Li, Baoyu; Liu, Yuwei; Guo, Xiaoyan (Frontiers in Nutrition, 2025)
BackgroundThe high-sensitivity C-reactive protein to albumin (CAR) ratio is a comprehensive measure of inflammation in vivo. Hepatic steatosis and fibrosis are significantly correlated with inflammation. The present study aimed to explore the possible associations between CAR and hepatic steatosis and fibrosis in the American population.MethodsThe study population involved the National Health and Nutrition Examination Survey (NHANES) participants from 2017 to 2020. The natural logarithm of CAR, calculated as Ln(CAR) with base “e,” was used for further analyses. The relationships between Ln(CAR) and the controlled attenuation parameter (CAP) and between Ln(CAR) and liver stiffness measurement (LSM) were investigated through multivariate linear regression analysis. Interaction and subgroup analysis identified factors affecting these variables. Nonlinear relationships were elucidated by smoothing curves and threshold effect analysis. Receiver operating characteristic (ROC) curve analysis was performed to evaluate the predictive performance of the CAR for non-alcoholic fatty liver disease (NAFLD). The results were adjusted for U.S. population estimates.ResultsThe study included a total of 7,404 individuals. Ln(CAR) was positively correlated with CAP in the fully adjusted model, with an effect value of β = 1.827 (95% CI, 0.611, 3.042). A more pronounced positive association was observed among participants with a BMI ≥ 25 kg/m2 in the subgroup analysis. An inverted U-shaped association was shown between Ln(CAR) and CAP through smooth curve fitting and a two-segment linear regression model, with an inflection point of (−9.594). ROC curve analysis showed that CAR had a moderate predictive value for NAFLD (AUC = 0.6895), with a sensitivity of 0.7276 and a specificity of 0.6092. No significant association was detected between Ln(CAR) and the LSM.ConclusionWe demonstrate an inverted U-shaped relationship between Ln(CAR) and CAP risk within the U.S. demographic. Our results suggest that CAR may serve as a valuable diagnostic tool for NAFLD. Further prospective research is necessary to validate this conclusion.